Penerapan Media Visual untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPS di Sekolah Dasar - Siti Junanah; Nurriska Safitri; Oman Farhurahman (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
This research aims to evaluate the extent to which the use of visual media can improve student learning outcomes in social studies learning at the elementary school level. This research has been carried out using descriptive qualitative research methods with data collection techniques, namely literature study. Data sources include books, journals or previous articles and theses that have the same theme as this research. This research shows that the use of visual media has a significant impact on improving student learning outcomes in social studies lessons in elementary schools. Visual media helps students visualize abstract concepts, so that learning material becomes more concrete and easier to understand. This not only improves student learning outcomes, but also encourages their involvement, motivation and creativity in the learning process. Thus, the use of visual media should be routinely integrated into learning activities to achieve optimal learning outcomes and improve the quality of good education at the elementary school level.